The effect of continuous electronic fetal monitoring on mode of delivery and neonatal outcome among low-risk laboring mothers at Debre Markos comprehensive specialized hospital, Northwest Ethiopia - Kebede, Tirusew Nigussie; Abebe, Kidist Ayalew; Chekol, Moges Sisay; Moltot Kitaw, Tebabere; Mihret, Muhabaw Shumye; Fentie, Bezawit Melak; Sibhat, Yared Alem; Tizazu, Michael Amera; Beshah, Solomon Hailemeskel; Taye, Birhan Tsegaw (Frontiers in Global Women's Health, 2024)
Background Electronic fetal heart rate monitoring (EFM) has been widely used in obstetric practice for over 40 years to improve perinatal outcomes. Its popularity is growing in Ethiopia and other sub-Saharan African countries to reduce high perinatal morbidity and mortality rates. However, its impact on delivery mode and perinatal outcomes in low-risk pregnancies remains controversial. This study aimed to assess the effect of continuous EFM on delivery mode and neonatal outcomes among low-risk laboring mothers at Debre Markos Comprehensive Specialized Hospital, Northwest Ethiopia. Methods A prospective follow-up study was conducted from November 20, 2023, to January 10, 2024. All low-risk laboring mothers meeting the inclusion criteria were included. Data were collected via pretested structured questionnaires and observation, then analyzed using Epi-data 4.6 and SPSS. The incidences of cesarean delivery and continuous EFM were compared using the chi-squared test and Fisher's exact test. Results The study found higher rates of instrumental-assisted vaginal delivery (7% vs. 2.4%) and cesarean sections (16% vs. 2%) due to unsettling fetal heart rate patterns in the continuous EFM group compared to the intermittent auscultation group. However, there were no differences in immediate neonatal outcomes between the groups. Conclusion When compared to intermittent auscultation with a Pinard fetoscope, the routine use of continuous EFM among low-risk laboring mothers was associated with an increased risk of cesarean sections and instrumental vaginal deliveries, without significantly improving immediate newborn outcomes. However, it is important to note that our study faced significant logistical constraints due to the limited availability of EFM devices, which influenced our ability to use EFM comprehensively. Given these limitations, we recommend avoiding the routine use of continuous EFM for low-risk laboring mothers to help reduce the rising number of operative deliveries, particularly cesarean sections. Our findings should be interpreted with caution, and further research with adequate resources is needed to draw definitive conclusions.